Ways to Develop Competent Skills in the Content of Natural Sciences in Students - Razzokova Ikhtiborkhan Mamirovna; Turdieva Odinakhan Mamirovna; Kakhkhorova Fatimakhan Kamiljon qizi (Researchparks Publishing, 2022)
The article describes innovative technologies for improving methodological competence in teaching natural sciences, unique pedagogical features of science teaching methodology, methodical ways of organizing creative works based on didactic goals and tasks of teaching.